Clinical Immunogenicity Evaluation of Eptinezumab, a Therapeutic Humanized Monoclonal Antibody Targeting Calcitonin Gene-Related Peptide (CGRP) for the Preventive Treatment of Migraine - Pederson, Susan; Biondi, David M.; Allan, Brent; Cady, Roger; Schaeffler, Barbara; Baker, Brian; Latham, John (Frontiers in Immunology, 2021)
Background: Eptinezumab is a humanized monoclonal antibody that selectively binds calcitonin gene-related peptide and is indicated for the preventive treatment of migraine in adults. This analysis characterizes the immunogenic profile of eptinezumab using data from clinical trials of eptinezumab for migraine prevention. Methods: Immunogenicity data were collected from five studies that included 2076 patients with episodic or chronic migraine treated with eptinezumab at dose levels ranging from 10 to 1000 mg, administered intravenously for up to 4 doses at 12-week intervals. Anti-drug antibody (ADA) results were available from 2074 of these patients. Four studies were randomized, double-blind, placebo-controlled trials with ADA monitoring for up to 56 weeks; one was a 2-year, open-label, phase 3 safety study with ADA monitoring for 104 weeks. Patients who had a confirmed ADA-positive result at the end-of-study visit were monitored for up to 6 additional months. Development of ADA and neutralizing antibodies (NAbs) were evaluated to explore three key areas of potential impact: pharmacokinetic exposure profile (eptinezumab trough plasma concentrations), efficacy (change in monthly migraine days), and safety (rates of treatment-emergent adverse events). These studies included methods designed to capture the dynamics of a potential humoral immune response to eptinezumab treatment, and descriptive analyses were applied to interpret the relationship of ADA signals to drug exposure, efficacy, and safety. Results: Pooled across the five clinical trials, treatment-emergent ADAs and NAbs occurred in 15.8 and 6.2% of eptinezumab-treated patients, respectively. Highly consistent profiles were observed across all studies, with initial onset of detectable ADA observed at the week 8 measurement and maximal ADA frequency and titer observed at week 24, regardless of eptinezumab dose level or number of doses. After 24 weeks, the ADA and neutralizing antibody (NAb) titers steadily declined despite additional doses of eptinezumab. Interpretation: Collectively, these integrated analyses did not demonstrate any clinically meaningful impact from ADA occurring after treatment with eptinezumab. The ADA profiles were low titer and transient, with the incidence and magnitude of ADA or NAb responses declining after week 24. Development of ADAs and NAbs did not impact the efficacy and safety profiles of eptinezumab.